The Role of Artificial Intelligence in Midwifery: A Scoping Review of Benefits, Challenges, and Ethical Implications - Cyril B. Romero; Ramil Edward V. Cariño; Charmae B. Ignacio (The Indonesian Institute of Science and Technology Research, 2025)
Artificial Intelligence (AI) is rapidly transforming healthcare and holds significant potential to improve maternal and neonatal outcomes through its application in midwifery. This scoping review investigates the role of AI in midwifery, emphasizing its benefits, challenges, and ethical implications. Guided by the Arksey and O’Malley framework, a systematic literature search was conducted using Google Scholar (2014–2024) via the Publish or Perish software, with keywords including